Autoantibodies Against Cell-Surface GRP78 Promote Tumor Growth in a Murine Model of Melanoma - de Ridder, Gustaaf G. (2011)
Autoantibodies that react with GRP78 expressed on the cell-surface of many tumor cell lines occur in the sera of patients with prostate cancer, melanoma, and ovarian cancer. These autoantibodies are a negative prognostic factor in prostate cancer, and when purified, stimulate tumor cell proliferation in vitro. It is unclear, however, whether these IgGs are merely a biomarker, or if they actually promote tumor growth in vivo. We immunized C57Bl/6 mice with recombinant GRP78 and then implanted the B16F1 murine melanoma cell line as flank tumors. We employed the antisera from these mice for in vitro cell signaling and proliferation assays. The immunodominant epitope in human cancer patients was well represented in the antibody repertoire of these immunized mice. We observed significantly accelerated tumor growth, as well as shortened survival in GRP78-immunized mice as compared to controls. Furthermore, antisera from these mice, as well as purified anti-GRP78 IgG from similarly immunized mice, stimulate Akt phosphorylation and proliferation in B16F1 and human DM6 melanoma cells in culture. These studies demonstrate a causal link between a humoral response to GRP78 and the progression of cancer in a murine melanoma model. They support the hypothesis that such autoantibodies are involved in the progression of human cancers and are not simply a biomarker. Because GRP78 is present on the surface of many types of cancer cells, this hypothesis has broad clinical and therapeutic implications.